The role of genre, identity, and rhetorical agency in the military writing of post-9/11 student-veterans - Hadlock, Erin D., author; Doe, Sue, advisor; Langstraat, Lisa, committee member; Grigg, Neil, committee member (Colorado State University. Libraries, 2012)
Since the Post-9/11 GI Bill was signed into law in August 2009, hundreds of thousands of student-veterans and more than $3.6 billion have poured into college campuses nationwide. Student-veterans have brought with them incredible life experiences, maturity, and self-discipline, as well as different learning styles and stressors that traditional students typically do not face. Recent qualitative research about this population has primarily been dedicated to their transitions and disabilities, but relatively few researchers have explored student-veterans' academic preparation acquired in those formative years in the military, especially skills in writing. Therefore, in this thesis, two colleagues and I survey and interview nine student-veterans, representing each branch of service, at Colorado State University. I explore their past textual production in the military and use those experiences with writing to shape and inform my discussion about genre use and theory as put forth by Amy Devitt and Anis Bawarshi. Because almost all writing in the military is formed within a specific genre, genres are central to the writing histories of student-veterans. In the military, genres serve not only as formatting guides but also as sites of cultural capital and rhetorical action, and they have a profound effect on how student-veterans construct meaning from writing in first-year composition classrooms. Additionally, I look to Michele Foucault's theories of constituted identities to explain how student-veterans' beliefs about writing are influenced by the communities in which they participate. The societal stratum in the military of officers and enlisted soldiers greatly determines what student-veterans understand as writing and its relationship to class-bound identities. My findings suggest, however, that as active duty soldiers, student-veterans used many of the rhetorical skills taught in a composition classroom but often have difficulty recognizing what they did as writing. Because few composition instructors are familiar with military text production, this thesis provides information about the connections between military and academic writing, identifies ideas about strengthening curricula, and suggests directions for future research.
Keywords: military; genre; rhetoric; student-veterans; veterans; writing